The red-shift-magnitude relation and observational data - Sherman, Windsor L.; United States. National Aeronautics and Space Administration; Langley Research Center (Washington, D.C. : National Aeronautics and Space Administration : [Springfield, Va. : For sale by the Clearinghouse for Federal Scientific and Technical Information, 1969)
Red shift-magnitude relation for universe model and observational data.
Prepared at Langley Research Center.
"August 1969."
Cover title.
Includes bibliographical references (p. 24-25).
Mode of access: Internet.
Keywords: Cosmology -- Mathematical models; Cosmography -- Mathematical models; Astronomy -- Observations; Cosmology; Red shift